The Protective Effect of Luteolin in Glucocorticoid-Induced Osteonecrosis of the Femoral Head - Yan, Zijian; Zhan, Jingdi; Qi, Weihui; Lin, Jian; Huang, Yijiang; Xue, Xinghe; Pan, Xiaoyun (Frontiers in Pharmacology, 2020)
Glucocorticoid-induced osteonecrosis of the femoral head (GIONFH) is a frequently occurring type of non-traumatic osteonecrosis. A failure of the timely treatment can eventually result in the collapse of the subchondral bone structure. Luteolin (Lut), a compound extracted from Rhizoma Drynariae, is reported to possess multiple pharmacological properties including anti-cancer, anti-oxidant, anti-apoptosis, and anti-inflammatory properties. However, whether Lut has a protective effect on the development of GIONFH remains unclear. In this study, we evaluated the effect of Lut on Dexamethasone (Dex)-induced STAT1/caspase3 pathway in vitro and evaluated GIONFH model in vivo. In vitro, Lut inhibited the upregulation of Dex-induced phospho-STAT1, cleaved caspase9, and cleaved caspase3. In addition, Lut inhibited Dex-induced expression of Bax and cytochrome c and increased the expression of B cell lymphoma-2(Bcl-2). In vivo, Lut decreased the proportion of empty lacunae in rats with GIONFH. Taken together, these findings indicate that Lut may have therapeutic potential in the treatment of GIONFH. Further, this effect might be achieved by suppressing mitochondrial apoptosis of osteoblasts via inhibition of STAT1 activity.